Prevalence of antibiotic resistance in commensal Escherichia coli among the children in rural hill communities of Northeast India. - Ashish Kumar Singh; Saurav Das; Samer Singh; Varsha Rani Gajamer; Nilu Pradhan; Yangchen Doma Lepcha; Hare Krishna Tiwari (PLoS ONE, 2018)
Commensal bacteria are the representative of the reservoir of antibiotic resistance genes present in a community. The usage of antibiotics along with the demographic factors is generally associated with an increase in antibiotics resistance in pathogens. Northeast (NE) India is untapped with regard to antibiotic resistance prevalence and spread. In the current study, the prevalence of antibiotic-resistant commensal Escherichia coli in pre-school and school-going children (n = 550, 1-14 years old) from the rural areas of the state of Sikkim-an NE Indian state, with respect to associated demographic factors was investigated. A total of 550 fecal E. coli isolates were collected during July 2015 to June 2017. A structured questionnaire was used to collect data to ascertain the potential factors associated with the carriage of antibiotic resistance E. coli among the children. Statistical analysis along with a logistic regression identified potential external factors affecting the observed antibiotic resistance pattern. The data indicated a high prevalence of resistance to common antibiotics like ampicillin (92%), ceftazidime (90%), cefoxitin (88%), streptomycin (40%) and tetracycline (36%), but no resistance to chloramphenicol. The resistance to the combination of penicillin and quinolone group of antibiotics was observed in fifty-two percent of the isolates. A positive correlation between the harboring of antibiotics resistant E. coli with different demographic factors was observed such as, with children living in nuclear family (vs joint family 63.15%, OR 0.18, 95% CI:0.11-0.28, p < 0.01), below higher secondary maternal education (vs college graduates 59.27% OR 0.75, 95% CI:0.55-1.02, p < 0.02). A close association between different demographic factors and the high prevalence of antibiotic-resistant commensal E. coli in the current study suggests a concern over rising misuse of antibiotics that warrants a future threat of emergence of multidrug-resistant pathogen isolates.